PERSPEKTIF MUSLIM PROGRESIF IJTIHADIS TENTANG NUSYUZ: APLIKASI TAWARAN METODOLOGIS ABDULLAH SAEED - Salam, Nor (STIT Sunan Giri Bima, 2022)
This study focuses on the application of Abdullah Saeed's methodological proposition to deconstruct the meaning of nusyuz. Nusyuz itself in the context of classical fiqh studies is often assumed to be a wife's disobedience to her husband, and therefore, in the face of this condition, a man is allowed to beat her. Through this study, the concept of nusyuz as indoctrinated in classical fiqh is considered to be contrary to efforts to protect women from various forms of violence. Thus, the act of beating must be interpreted as a husband's indifference to his wife.